2009
DOI: 10.1016/j.bbrc.2009.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Selective cytotoxicity of a bicyclic Ras inhibitor in cancer cells expressing K-RasG13D

Abstract: Mutation of RAS genes is a critical event in the pathogenesis of different human tumors and in some developmental disorders. Here we present an arabinose-derived bicyclic compound displaying selective cytotoxicity in human colorectal cancer cells expressing K-Ras(G13D), that shows high intrinsic nucleotide exchange rate. We characterize binding of bicyclic compounds by docking and NMR experiments and their inhibitory activity on GEF-mediated nucleotide exchange on wild-type and mutant Ras proteins. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…[76] To improve their water solubility and potency, derivatives were designed which can inhibit RasGRF-1-catalyzed nucleotide exchange in vitro (half-maximum inhibitory concentration (IC 50 ) = 35-80 mm). [77] Reduced cell growth in Ras-dependent cell lines as well as decreased downstream signaling were observed at high micromolar concentrations,but the exact mode of action still remains elusive and off-target effects have to be considered in certain cases.F or another compound of the SCH compound family (SCH51344 (9), Figure 5a)which was reported to modulate the Ras signaling pathway through an ovel mechanism, [78] the human mutT homologue hMTH1 was recently identified as the actual target. [79] Based on the Ras-binding epitopes of its GEFs,rationally designed orthosteric peptidic inhibitors were developed to impair Ras nucleotide exchange.…”
Section: Ras Gtpasesmentioning
confidence: 98%
“…[76] To improve their water solubility and potency, derivatives were designed which can inhibit RasGRF-1-catalyzed nucleotide exchange in vitro (half-maximum inhibitory concentration (IC 50 ) = 35-80 mm). [77] Reduced cell growth in Ras-dependent cell lines as well as decreased downstream signaling were observed at high micromolar concentrations,but the exact mode of action still remains elusive and off-target effects have to be considered in certain cases.F or another compound of the SCH compound family (SCH51344 (9), Figure 5a)which was reported to modulate the Ras signaling pathway through an ovel mechanism, [78] the human mutT homologue hMTH1 was recently identified as the actual target. [79] Based on the Ras-binding epitopes of its GEFs,rationally designed orthosteric peptidic inhibitors were developed to impair Ras nucleotide exchange.…”
Section: Ras Gtpasesmentioning
confidence: 98%
“…5.5) [25]. Other generations of type 1 and 2 compounds were synthesized with a 3,4 dihydroxyphenyl (3,4 catechol) group replacing phenylhydroxylamine and STD experiments consistently indicated the involvement of benzyl ether and catechol groups in the interaction with Ras ( Fig.…”
Section: Nmr Binding Experimentsmentioning
confidence: 94%
“…5.5) showed that in high-scoring poses, all compounds bind Ras in a cleft near the Switch 2 region [25]. 5.5) showed that in high-scoring poses, all compounds bind Ras in a cleft near the Switch 2 region [25].…”
Section: Docking Analysismentioning
confidence: 99%
“…Later, Ras neutralizing antibodies were employed as oncogenic Ras blockers in cell culture experimentation [24-26] and mutant Ras epitopes were exploited for their suitability as antigens in the development of cancer vaccines [27]. Further approaches to target oncogenic Ras rested on antisense oligonucleotides directed to the Ras mRNA [28], and more recently on exploiting structural information and improved in silico approaches to identify and target druggable pockets or moieties that affect Ras nucleotide exchange [29,30], Ras activation [31,32], effector interaction [33,34] or binding to escort proteins critical for subcellular trafficking [35]. Moreover, numerous studies have targeted Ras downstream effector pathways such as Raf kinases, MEK or PI3Ks [36,37].…”
Section: Introductionmentioning
confidence: 99%